Simmons, Betty. New Perlican Photograph of two men and a child. - Barrett, Terra
A photograph of James Legge on accordion (left), the child is Noel Smith (middle), and Clarence Legge, James' son (right). Each is sitting on a chair, James is playing accordion, Noel is holding a small accordion, and Clarence is sitting next to them.